Politologia wobec feminizmu a feminizm wobec politologii - KOŁODZIEJCZAK, Magłorzata (Przegląd Politologiczny, 2018)
The paper discusses the issue of the complex relationship between political science as a branch of academia and modern trends in feminism, understood as a collection of mutually related ideologies. The author emphasizes that both science and ideology are forms of politi- cal practice exercised in the same social and political reality. However, they are fundamen- tally different with respect to the hierarchy of their functions. The ‘clash’ of these two products of human activity produces political science on women and the politological analysis of feminism (subjected first and foremost to the scientific function) on the one hand, and various proposals of feminist modifications of political science that produce feministically re- formed political science and gynocentric political science (where the scientific function is subjected to social objectives) on the other.